A Career Success of the Distributors in Multi-Level Marketing (MLM) Company - Siahaan, Elisabet; ., Yasmin Chairunisa M. (Information Management and Business Review, 2014)
Nowadays, MLM Company around the world are highly developed, and companies especially in Indonesia have been using a system of direct sales to the consumers. The career structure in MLM Company has been very much acknowledged. However, not all MLM distributors are able to achieve the line of succession. The purpose of this research is to analyse the main causes of career success in MLM Company. This study uses both quantitative and qualitative methods. The selection of samples is carried out using a snowball technique which retrieved as many as 198 distributors registered at the Multi-Level Marketing (MLM) Company in Medan, namely; PT. Herbalife Indonesia, PT. Orindo Ayu (Oriflame), PT. Sophi Martin Indonesia, PT. K-link, PT. Tupperware Indonesia and PT. Amway Indonesia. The result of the study finds that entrepreneurial competency and committment simultaneously have a significant influence to the career success of MLM distributors. Moreover, the study finds a partial relationship between the entrepreneurial commitment and motivation that has a significant effect on career success, while the entrepreneurial competency does not partially influence the success of career significantly. The results also show that entrepreneurial motivation is a moderating variable that is able to strengthen the influence of the entrepreneurial commitment to career success, as well as between the entrepreneurial competency and career success.